Le palmier à huile en plantation villageoise - Jacquemard, Jean-Charles (éditions Quae, 2013)
The oil palm food-processing sector relies hugely on village plantations. Intended especially for small oil palm planters, this book provides the technical and practical bases for creating and developing their palm stand. It is organised into 44 sheets covering all aspects: pre-nursery, nursery, creating the plantation, young crops, plantation in production, harvesting clusters, main accidents (diseases, pests, nutrition), safety.